Synthesis and Characterization of Magnetite Nanofiber for Magnetic Field Sensor - Nabila Putri Aulia; Arif Hidayat; Ahmad Taufiq (JPSE (Journal of Physical Science and Engineering), 2024)
This study reports the performance of a magnetite sensor using magnetite nanofibers. Magnetite nanoparticles, synthesized from natural iron sand via coprecipitation and integrated into a polyvinylidene fluoride matrix by electrospinning. Structural analysis confirmed by x-ray diffraction (XRD), scanning electron microscopy (SEM), and fourier transform infrared (FTIR) characterizations. The nanofiber had an average diameter of 618.4 nm. The results of the magnetic property analysis showed that the nanofiber was superparamagnetic with a saturation magnetization value of 15.04 emu/g. The sensor exhibited good sensitivity and resolutions with a value 3.31 mV/mT and 0.015 mT with excellent stability.